Implementation Effectiveness Of Police Role In Eradication Of Online Gaming Crime In Digital Era - Edward Cevy Listiyanto; Arpangi Arpangi (Law Development Journal, 2021)
This study aims to analyze juridically regarding the effectiveness of eradicating the crime of online gambling in the jurisdiction of the Grobogan police station. The method in this research is sociological juridical. Based on the analysis carried out, law enforcement cannot be carried out because there are no reports from the public accompanied by evidence. This has resulted in an ineffective eradication of online gambling crimes in jurisdictions including the Grobogan Police. Cyber crime is defined as an illegal activity with computer intermediaries carried out through a global electronic network. Online gambling is categorized as a cyber crime because in committing the crime, online gambling uses computers and the internet as a medium to commit the crime of gambling. Gambling is basically against religious norms, decency, and Pancasila morals, and can be dangerous for the survival of the community, nation and state. Gambling is a violation of social culture in Indonesia. Proof of online gambling can be done using proof of transfer and e-mail. Act No. 11 of 2008 Article 5 paragraph (1) which states that Electronic Information and/or Electronic Documents and/or their printouts are legal evidence.